2006
DOI: 10.1002/ejic.200600348
|View full text |Cite
|
Sign up to set email alerts
|

Can the Clusters Zr6O4(OH)4(OOCR)12 and [Zr6O4(OH)4(OOCR)12]2 Be Converted into Each Other?

Abstract: Keywords: Zirconium / Zirconium oxo cluster / Hafnium oxo cluster / Metal carboxylate / Ligand exchange 12 ] 2 is also reported for comparison. The Zr12 clusters are structurally related to the Zr6 clusters since they are composed of two Zr6 sub-units which are bridged by four carboxylate ligands. In each compound, carboxylic acid molecules interact with the cluster by hydrogen bonding to part of the µ 3 -OH ligands. The clusters are highly dynamic in solution, due to site exchange of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(157 citation statements)
references
References 13 publications
(42 reference statements)
7
139
1
Order By: Relevance
“…3. The molecular formula is indicative for [Zr 6 O 4 (OH) 4 (CH 3 CH 2 COO) 12 ] 2 (2xZr6), similar to the ones described by Puchberger and coworkers [17]. The unit cell contains two independent molecules.…”
Section: Crystal Structurementioning
confidence: 92%
“…3. The molecular formula is indicative for [Zr 6 O 4 (OH) 4 (CH 3 CH 2 COO) 12 ] 2 (2xZr6), similar to the ones described by Puchberger and coworkers [17]. The unit cell contains two independent molecules.…”
Section: Crystal Structurementioning
confidence: 92%
“…UiO-66 shows excellent chemical and thermal stabilities in various solvents (water, DMF, and alcohols), and strong structural resistance against mechanical pressure (>10,000 kg/cm 2 ) [14]. UiO-66 has been tested for adsorption, separation, and catalysis after various post-synthesis modifications [20][21][22][23][24][25][26]. Kim et al first reported the modification of UiO-66-Br to UiO-66-CN via microwave irradiation [26] as well as tandem functionalization with a mixed ligand UiO-66-(Br)(NH 2 ) [27].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Most of the described actinide(IV) complexes are hexanuclear, similar to the hexanuclear nanosized clusters of transition metal complexes. [16][17][18] These clusters have attracted an intense interest because of their important applications in materials science, especially as potential precursors, which can be applied in magnetic, electronic and catalytic processes. [19,20] Recent attempts to synthesize hexameric U complexes used predominately aprotic solvents.…”
Section: Introductionmentioning
confidence: 99%